Odpowiedzi

2010-03-02T14:54:56+01:00
A)2x-(-4-3x)= 2x+4+3x=5x+4
b)10-2(t+1)= 10-2t-2=-2t+8
c)-3(2y+1/3)+4y= -6y-1+4y=-2y-1
d)-6(1-0,5u)+3u= -6+3u+3u=6u-6

2
e)2(3w-1)-w+2= 6w-2-w+2=5w

2
f)3(a-2b)-5(b-2a)=3a-6b-5b+10a=13a-11b
15 3 15
  • Użytkownik Zadane
2010-03-02T15:00:42+01:00
A) 2x-(-4-3x) = 2x+ 4 -3x= -1x + 4
b)10-2(t+1) = 10- 2t -2= 8- 2t
c)-3(2y+1/3)+4y = -6y - 1 + 4y= -2y -1

d)-6(1-0,5u)+3u
---------------------- =
2

-6 + 3u + 3u
= ---------------- =
2

-6 + 6u
= ------------ =
2

= -3 + 3u


e)2(3w-1)-w+2
---------------------- =
2

6w -2 -w +2
= ----------------- =
2

= 5w :2 = 2,5 w

f)3(a-2b)-5(b-2a) = 3a - 6b - 5b + 10a= 13a - 11b ;)
6 1 6
2010-03-02T15:01:14+01:00
A) 2x-(-4-3x)=
=2x+4+3x=
=5x+4
b) 10-2(t+1)=
=10-2t-2=
=8-2t
c) -3(2y+1/3)+4y=
=-6y-1+4y=
=-2y-1
d) -6(1-0,5u)+3u=
=-6+3u+3u=
=6u+6
e) 2(3w-1)-w+2=
=6w-2-w+2=
=5w
f) 3(a-2b)-5(b-2a)
=3a-6b-5b+10a=
13a-11b

Prosze :))
8 3 8